(3TQW GdEeGe UGMH GdcTas
(3ChdgG (B:s
(3GdTQW gh GdYdGeg hCTQGW GdSGYI YdGeGJgG ceG bGd Ef gPg CTQGW GdbjGeg hCReJgG hbGd ai GddZI CTQGWgG YdGeGJgG s
(3BNQgG (B:s
(3hJeJO ef GdeYjf GdfUjQ Ydi bgQ GdTghGJ GdaGfjI hEPG JhLg GdYHO Edi GdQH SHMGfg HSGOb WhjJg agh jYjfg hjbhjg hdG jRNQg Yef s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs